Mr. Roman's Spuriosity Shop: A Thematic Catalog - Bengtsson, I. (Stockholm Swedish Music History Archive, 1976)
The book lists incipits and other excerpts from compositions by more than sixty composers, some of which were misattributed or of uncertain origin, hence the "spuriosity".
Keywords: Catalog